2020
DOI: 10.1007/s41999-020-00432-w
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 mortality risk factors in older people in a long-term care center

Abstract: Aim COVID-19 mortality risk factors in older people from a long term care center. Findings Male gender, low Barthel index, no pharmacological treatment and lymphocytopenia are independent mortality risk factors. Message The independent prognostic factors identified in the present study can help to adjust the healthcare resources in this population in case of new outbreaks of the COVID-19 pandemic.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 31 publications
(34 reference statements)
0
45
0
2
Order By: Relevance
“…Incidence, demographic associations [ 20 ], transmission and symptom status [ 9 , 10 , 11 , 12 , 13 , 15 , 16 , 19 ], and atypical presentation [ 17 , 18 , 21 ] in LTCF residents are widely discussed in the literature [ 14 ]. Less attention was paid to the clinical patterns of COVID-19 in LTCF residents, as it relates to mortality outcomes, and those that did were not in exclusively outpatient settings [ 22 , 23 ]. The unique combination of a congregate outpatient setting, staff interaction, and resident characteristics suggests differences in exposure, illness course, and risk of sequelae like venous thromboembolisms, when compared to hospitalized or community-dwelling patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incidence, demographic associations [ 20 ], transmission and symptom status [ 9 , 10 , 11 , 12 , 13 , 15 , 16 , 19 ], and atypical presentation [ 17 , 18 , 21 ] in LTCF residents are widely discussed in the literature [ 14 ]. Less attention was paid to the clinical patterns of COVID-19 in LTCF residents, as it relates to mortality outcomes, and those that did were not in exclusively outpatient settings [ 22 , 23 ]. The unique combination of a congregate outpatient setting, staff interaction, and resident characteristics suggests differences in exposure, illness course, and risk of sequelae like venous thromboembolisms, when compared to hospitalized or community-dwelling patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies on COVID-19 outbreaks in the institutionalized elderly largely focus on epidemiological characteristics [ 9 , 10 , 11 , 12 ] and clinical symptoms related to initial presentation and transmission [ 13 , 14 , 15 , 16 , 17 , 18 ]. Few studies assessed the clinical course and past initial symptom status of residents, as it relates to mortality outcomes [ 19 , 20 , 21 ], especially in a non-hospital setting [ 22 , 23 ], with an infection and mortality rate as high as those documented here. In this study, we report a COVID-19 outbreak among 116 residents of a nursing home with a very high infection and mortality rates, with a specific focus on the clinical presentation and characteristics associated with mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Several conditions are associated with increased virus susceptibility and worse outcomes, advanced age being the most important. In elderly patients, mortality associated with COVID-19 varies widely among different countries, but patients older than 65 consistently comprise the majority of total deaths [ 2 , 3 , 4 , 5 ]. Mortality, in this subset of the population, is reported to be 8–36%, depending on the country and age interval analyzed [ 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heras et al reported on COVID-19 patients from a single nursing home in Spain. 4 This was designed as a retrospective cohort case-controlled analysis. There were 100 confirmed cases and a medicalization approach to treatment had been carried out in 83 subjects.…”
Section: Resultsmentioning
confidence: 99%